Editorial - Anna Oksiutycz (Communicare)
With the current edition, change comes to Communicare as we strive to respond to the needs of our readers, contributors and the broad academic community. For many years Communicare has been publishing articles from beyond Southern Africa. The articles published in the journal are read worldwide, so it is only fitting that the title of the journal has changed from Communicare: Journal for Communications Sciences in Southern Africa to Communicare: Journal for Communication Studies in Africa. Since its inception in 1980, Communicare has been a subscription journal, but this year we are leaping into the future as the journal has become an open access journal. Open access publishing in recent decades has become a growing trend in publishing (Laakso 2011). Furthermore, globally, an increasing number of research funding agencies, especially those that rely on public funding, mandate publishing research findings under open access model (The Economist 2018).